2005
DOI: 10.1108/15265940510633505
|View full text |Cite
|
Sign up to set email alerts
|

The effect of capital structure on profitability: an empirical analysis of listed firms in Ghana

Abstract: Purpose -This paper seeks to investigate the relationship between capital structure and profitability of listed firms on the Ghana Stock Exchange (GSE) during a five-year period. Design/methodology/approach -Regression analysis is used in the estimation of functions relating the return on equity (ROE) with measures of capital structure. Findings -The results reveal a significantly positive relation between the ratio of short-term debt to total assets and ROE. However, a negative relationship between the ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

90
580
21
38

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 636 publications
(818 citation statements)
references
References 33 publications
90
580
21
38
Order By: Relevance
“…Champion (1999) concluded that companies can use more debt to enhance their financial performance because of debts' capability to cause managers to improve productivity to avoid bankruptcy. Abor (2005) found a significantly positive relationship between total debt and profitability. Roden and Lewellen (1995) used a sample of 48 U.S. firms for the period [1981][1982][1983][1984][1985][1986][1987][1988][1989][1990] and found a positive relation between profitability and capital structure.…”
Section: The Static Trade-off Theorymentioning
confidence: 90%
“…Champion (1999) concluded that companies can use more debt to enhance their financial performance because of debts' capability to cause managers to improve productivity to avoid bankruptcy. Abor (2005) found a significantly positive relationship between total debt and profitability. Roden and Lewellen (1995) used a sample of 48 U.S. firms for the period [1981][1982][1983][1984][1985][1986][1987][1988][1989][1990] and found a positive relation between profitability and capital structure.…”
Section: The Static Trade-off Theorymentioning
confidence: 90%
“…With respect to short-term debt, it is generally expected that firms tend to match the maturity of their debts with assets. This means that firms with more fixed assets rely more on long-term debt, while those with more contemporary assets depend more on short-term financing (Abor 2005).…”
Section: Estimation Results Of De Model With a Robust Standard Errormentioning
confidence: 99%
“…Capital structure decision is important because it affects the financial performance of the firm. The capital structure of a firm is defined as specific mix of debt and equity that a firm uses to finance its operations [1].…”
Section: Introductionmentioning
confidence: 99%